Mushroom Bodies, Ca(2+) Oscillations, and the Memory Gene amnesiac. - Davis, R.L. (Neuron, 2001)
The memory of odors in Drosophila is mediated by mushroom body neurons. Memory is formed, in part, by a modulation of the physiology of these neurons brought about by neuropeptides that are encoded by the amnesiac gene and released from peptidergic neurons that innervate mushroom body neurons. Slow and spontaneous oscillations of calcium levels are elevated in the mushroom body neurons of amnesiac mutants and may contribute to memory consolidation.